The Spillover Effect Evaluation of Chinese Emissions Trading Scheme - Li, Xinwu; Wang, Chan; Liao, Lianggui; Wen, Hongxin (Frontiers in Energy Research, 2021)
The carbon emissions trading scheme (ETS) is becoming a crucial policy in mitigating global climate change. This paper purposes to evaluate the spillover effect of Chinese ETS policy with the data of 30 provinces’ carbon emissions in China by China-MRIO model and input-output analysis. The MRIO model provides the change in production value in each region in the intermediate demand and final demand. 2012 and 2015 were selected as case study years to highlight the spillover effects of ETS policy. The results show that some pilot regions such as Beijing, Tianjin, Shanghai, and Chongqing reduced their directed CO2 emissions while Guangdong and Hubei increased their directed CO2 compared to 2012. However, there were places like Hebei, Shanxi, Inner Mongolia, Ningxia, and Xinjiang that undertook a mass of embodied CO2 emissions which were majorly caused by providing intermediate products. Similarly, the pilot regions transferred out CO2 emissions by using a good deal of intermediate products. Thus, it is argued that carbon transfer evaluation can provide scientific support for carbon allowance formulating and it is important for policymakers to consider embodied carbon emissions in intermediate product trading when allocating carbon allowance under the market strength of ETS.